“Diseño del sistema de generación eléctrica conectado a la red utilizando paneles fotovoltaicos para el autoconsumo de la Unidad Educativa Fiscomisional La Dolorosa” - Sozoranga Benítez, Edwin Marcelo (2024)
This work consists of the design of a photovoltaic generation system connected to the distribution network for self-consumption of the Unidad Educativa Fiscomisional "La Dolorosa" (UEFLD), located in the parish of El Sagrario, Canton of Loja, Province of Loja. The evaluation of the solar resource (solar radiation), according to data obtained from the National Aeronautics and Space Administration (NASA), has an average value of 4.27 kWh/m2 in the Canton of Loja. For this reason, the design of an electric power generation system was proposed as an alternative to reduce costs, take advantage of renewable energy and contribute to the reduction of greenhouse gasses. The size of the photovoltaic system that will be connected is determined by the lat/long coordinates of the site and the maximum power consumption of the UEFLD, which will help determine the number of solar panels needed and the selection of the appropriate converter. The methodology used for the projection of this work, consists of the collection, analysis of research and data processing for the selection of each element. In addition, the economic analysis of the presented proposal is carried out, regarding the recovery of the investment; and finally, the commercialization of the photovoltaic system connected to the grid is analyzed. Keywords: Photovoltaic generation system, solar energy, self-consumption, electricity generation.